Reliability and Forced Outages: Survival Analysis with Recurrent Events - Ravago, Majah-Leah V (Archīum Ateneo, 2023)
This paper empirically investigates the contributory factors to forced outage declarations of power plants through a survival analysis model with recurrent events. Using plant-level data in the Philippines, we find that higher reserve margins, higher share capacity (a measure of concentration), and the number of planned outages and days since the last maintenance (preventive maintenance indicators) reduce the risk of forced outages. On the other hand, an increase in the use rate (a measure of the intensity of power plant utilization) and geothermal, solar, and biodiesel plants correlate positively to more forced outages. Focusing on episodes where outages were disproportionately higher in the past decade— we find that thinning reserve margin correlates significantly to forced outage incidence. We also find that a higher share of a power firm's capacity to the system's total dependable capacity contributes to lowering the risk of forced outages.